The Influence of Halal Tourism on Indonesia’s Economic Growth - Tutik Sukmalasari Putri; Muhammad Wakhid (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2023)
Purpose: This study aims to determine the effect of Halal Tourism on economic growth in Indonesia, calculated by the indicators of the number of foreign tourists, the number of foreign guests staying at star hotels, the number of domestic guests staying at star hotels. Method: The research method used is Multiple Linear Regression analysis. The independent variables in this study consist of the number of foreign tourist visits, the number of foreign guests staying, the number of domestic guests staying, and the dependent variable, namely economic growth in Indonesia from 2010-2021. Testing is done through classical testing and hypothesis testing. Results: The results showed that in a stimulant manner the number of foreign tourist visits had a positive and insignificant effect on economic growth, the variable effect of the number of foreign guests staying at star hotels had a positive and insignificant effect on economic growth, and the variable the number of domestic guests staying at star hotels had a positive effect and significant to economic growth in Indonesia. Contribution: This research contributes to building sharia tourism by paying more attention to attractions, accessibility, accommodation and policies that are clear and in accordance with sharia principles. Halal tourism will make a greater contribution to the Indonesian economy.